TRANSLATION ANALYSIS OF IDIOMATIC EXPRESSION IN THE AMAZING SPIDERMAN MOVIE - Muhammad Arly; Evert H. Hilman (PROJECT (Professional Journal of English Education), 2023)
This research aims to evaluate the translation techniques used by translators and in the film The Amazing Spiderman. The author applies a qualitative approach, and to collect data, the film script is sourced from the internet and then dissected using Mona Baker's theory (2018). There are 6 types of idioms quoting Baker, namely: Using idioms with similar meanings and forms, Using idioms with similar meanings but different forms, Borrowing idioms from the source language, Translation with paraphrases, Translation by removing idiom play, and Translation by removing all idioms. From this research it is known that only five out of six idioms appear in the film: (1) Using idioms with similar meanings and forms (17%), (2) Using idioms with different meanings and forms (33%). ), (3) Translation with paraphrase (24%), (4) Translation with omission of idiomatic plays (13%), and (5) Translation with omission of all idioms (13%). Keywords:  Idiomatic Expression; Movie; Translation Techniques